Lecturer Insights on Implementing Project-Based Learning at Jambi University - Reli Handayani; Mukhlash Abrar; Friscilla Wulan Tersta; Sukarno, Berliana Sukma Tri (Kajian Linguistik dan Sastra, 2024)
This study investigates lecturers' perspectives on Jambi University's implementation of Project-Based Learning (PjBL). The study underlines the significance of PjBL in improving student engagement, critical thinking, and problem-solving abilities, as well as the growing demand for creative teaching strategies in light of the digital transformation of the twenty-first century. Using a qualitative case study approach, the study collected data from 11 lecturers across different language education programs through observations and interviews. Key findings indicate that PjBL is perceived as an effective, student-centered learning method that fosters collaboration and practical problem-solving. The lecturers highlighted the relevance of projects to real-world issues and emphasized the importance of collaboration between students and faculty. Challenges in implementing PjBL were noted, particularly in training, resources, and shifting from traditional teaching methods. Overall, the study reveals that while lecturers recognize the benefits of PjBL, there is a need for ongoing support to maximize its potential in higher education.